2021
DOI: 10.3390/f12060678
|View full text |Cite
|
Sign up to set email alerts
|

Field Performances of Mediterranean Oaks in Replicate Common Gardens for Future Reforestation under Climate Change in Central and Southern Europe: First Results from a Four-Year Study

Abstract: Climate change imposes severe stress on European forests, with forest degradation already visible in several parts of Europe. Thus adaptation of forestry applications in Mediterranean areas and central Europe is necessary. Proactive forestry management may include the planting of Mediterranean oak species in oak-bearing Central European regions. Five replicate common gardens of Greek and Italian provenances of Quercus ilex, Q. pubescens and Q. frainetto seedlings (210 each per plantation) were established in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Q. pubescens is a semi-deciduous species that can withstand water limitation, with recent studies showing that it can be as resistant to drought stress as evergreen oaks such as Quercus ilex [84]. Q. frainetto, on the other hand, seems to be less tolerant to drought compared with the two other oaks in the study [85]. This ecophysiological knowledge seems to agree with the projected relative habitat loss in our study (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Q. pubescens is a semi-deciduous species that can withstand water limitation, with recent studies showing that it can be as resistant to drought stress as evergreen oaks such as Quercus ilex [84]. Q. frainetto, on the other hand, seems to be less tolerant to drought compared with the two other oaks in the study [85]. This ecophysiological knowledge seems to agree with the projected relative habitat loss in our study (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The measurements were performed in oaks seedlings of an existing common garden experiment, established within the FutureOaks project (more details given by Bantis et al 2021). In this project, Mediterranean oaks of identical accessions were evaluated for their potential as alternative tree species for altitudinal and latitudinal assisted migration.…”
Section: Site Description and Plant Materialmentioning
confidence: 99%
“…Q. frainetto is generally regarded as less drought-resistant compared to Q. pubescens, as quite a low leaf water potential levels cannot be avoided even with almost complete stomatal closure during severe drought (Fotelli et al 2000, Siam et al 2009. Consistently, lower photosynthetic rates, water-use efficiency, predawn leaf water potentials, and finally, growth and survival are reported for Q. frainetto vs. Q. pubescens (Bantis et al 2019(Bantis et al , 2021Pollastrini et al 2020). The higher drought sensitivity of Q. frainetto is also indicated by changes in chlorophyll fluorescence parameters, such as a decline of the performance index PIabs (Bantis et al 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Common gardens and provenance trials are an experimental approach offering longterm information regarding the potential of different forest species and origins to adapt to future climate. In order to assess the suitability of different Mediterranean oak species for potential assisted migration schemes in central Europe, Bantis et al [5], established a four common garden experiment and evaluated the early field performance of oak seedlings of different species and provenances. Based on survival rates, morphological, and physiological features, they concluded that Quercus pubescens may be a suitable candidate forest tree for poor and dry soils under the expected summer heat and drought conditions in Central Europe.…”
Section: Tree Adaptive Responses To Climatic Variabilitymentioning
confidence: 99%